Asteroid Bodies Associated with Granulomatous Meningoencephalitis in a Female Dog - Silva, Juneo F.; Serakides, Rogéria; Moreira, Matheus V. L.; Ocarino, Natália M. (Brazilian Journal of Veterinary Pathology, 2014)
A case of asteroid bodies associated with granulomatous meningoencephalitis is reported in a 4-year-old female dachshund that showed intermittent tremors and blindness. Necropsy revealed leptomeninges moderately hyperemic and from the parietal cortex extending into the temporal and frontal cortex, thalamus and midbrain flattening of the gyri and a grayish and friable focally extensive area. Microscopically intense and extensive perivascular inflammatory infiltrates of lymphocytes, plasma cells, macrophages and giant cells were observed. In the cytoplasm of the giant cells, neuropil stellate structures ranging from 20 to 80 μm in diameter with a central dense and homogenous zone and with amphophilic and vacuolated cytoplasm consistent with asteroid bodies were present. Special staining and transmission electron microscopy permitted the diagnosis of asteroid bodies associated with granulomatous meningoencephalitis.